Angler perceptions of pelican entanglement reveal opportunities for seabird conservation on fishing piers in Tampa Bay - B. Alexander Simmons (PLoS ONE, 2025)
Injuries from entanglement in marine debris are a significant threat to seabirds globally, and fishing gear is the most common debris affecting seabirds. In Tampa Bay, Florida, entanglement of brown pelicans (Pelecanus occidentalis) at fishing piers has been a highly contentious issue for years, especially at the Skyway Fishing Pier State Park. With entanglements continuing to rise, new fishing regulations were adopted at the pier to reduce the likelihood of severe entanglements, which include a controversial seasonal ban on certain high-risk fishing gear during the pelican breeding season. To better understand the extent of this problem and identify potential leverage points for promoting behavioral change, this study analyzed data on pelican condition and abundance near the south Skyway Fishing Pier, as well as data from questionnaires conducted on the pier capturing anglers’ perceptions of the issue and several proposed solutions, including the new gear restrictions. The results suggest a potential attraction of pelicans to anglers, with entanglement risks greatest at peak locations and times of angler activity. However, results from the angler surveys highlight several opportunities for minimizing these risks. Overall, anglers are generally concerned about the issue, believe others are also concerned, and supportive of educational videos and greater enforcement or punishment for people feeding pelicans. Anglers had mixed opinions on the new gear restrictions. Five types of anglers were identified using audience segmentation techniques, with each type representing a different potential target audience for promoting behavior change on the pier. Depending upon the audience, strategic messages using frames that focus on leadership or self-identity may be most effective for increasing the number of anglers who can safely rescue a hooked bird. Recommendations for future analyses and pilot social marketing campaigns are discussed to support further investigation into the human dimensions of seabird conservation in Tampa Bay.